IDENTIFIKASI POTENSI AIR TANAH MENGGUNAKAN METODE RESISITIVITAS KONFIGURASI SCHLUMBERGER DI KECAMATAN BONTORAMBA KABUPATEN JENEPONTO - Agussalim Agussalim; Andi Syam Rizal (JFT : Jurnal Fisika dan Terapannya, 2021)
Drought usually occurs, especially during the dry season in Bontoramba, Jeneponto Regency, South Sulawesi. Therefore, it is necessary to study the potential of groundwater to meet the water needs of the Bontoramba community during the dry season. A way to identify groundwater is by using the resistivity method. This method is applied with Schlumberger configuration that gives good results vertically. The purpose of this study was to identify the potential for groundwater both in position and depth based on the results of the interpretation of measurements using the resistivity method of the Schlumberger configuration. This research is experimental research with a descriptive method. Data were processed, analyzed, and interpreted using Res2dinv. Through the results of this interpretation, modeling of the distribution of the aquifer layer in the soil is then carried out which is projected as groundwater. The results showed that the groundwater layer in path 1 and path 2 were on average at a depth of 10-30 m, path 3 and path 4 at a depth more than 30 m from the ground surface.